Long-term disease-free survivor of metastatic large-cell neuroendocrine carcinoma of the lung treated with amrubicin and irinotecan - Ryuge, Shinichiro (Dove Medical Press, 2009)
Large-cell neuroendocrine carcinoma (LCNEC) is a relatively uncommon variant of non-small cell lung cancer. Since the biological characteristics of LCNEC are similar to those of small cell lung cancer, LCNEC is usually treated with chemotherapy regimens used for small cell lung cancer. However, the outcomes are usually dismal. Here, we report a patient with LCNEC (a metastasis to the brain). After whole brain irradiation, he received a combination of amrubicin and irinotecan chemotherapy, and has been relapse-free for two years. This treatment regimen may be beneficial for patients with advanced LCNEC.